The cinema of Yakov Protazanov - Wilson, F. Booth (Global film directors., 2024)
"Best known for Aelita (1924), the classic science-fiction film of the Soviet silent era, Yakov Protazanov directed over a hundred films in a career spanning three decades. Called "the Russian D.W. Griffith" in the 1910s for his formative role in the first movies in the last years of the Russian Empire, he fled the Civil War and maintained a successful career in Europe before making an unusual decision to return to Russia now under Soviet power. There his films continued their remarkable success with audiences undergoing a bewildering and often brutal revolutionary transformation. Rather than treating him as an indistinct, if capable craftsman, The Cinema of Yakov Protazanov argues that his films are suffused with a unique creative vision that reflects both his mindset as a traditional Russian intellectual and his experience of dislocation and migration after 1917. As he adapted his films to revolutionary culture, they intermingled different voices and reinterpreted his past work from a disavowed era. Offering fresh perspectives of Protazanov's films, the book will give readers a new appreciation of his career. The book offers a uniquely valuable vantage point from which to explore how cinema reflected a society in transformation and a seminal moment in the development of cinematic art"--